Antimicrobial susceptibility, risk factors and prevalence of bla cefotaximase, temoneira, and sulfhydryl variable genes among Escherichia coli in community-acquired pediatric urinary tract infection - Nisha, Kallyadan V.; Veena, Shetty A.; Rathika, Shenoy D.; Vijaya, Shenoy M.; Avinash, Shetty K. (Journal of Laboratory Physicians, 2017)
INTRODUCTION: The emergence of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli has become an important challenge among pediatric patients with community-acquired urinary tract infection (UTI).OBJECTIVES: The aim of this study was to assess the antimicrobial susceptibility patterns, associated risk factors and to survey the frequency of bla cefotaximase (CTX-M), bla temoneira (TEM), and bla sulfhydryl variable (SHV) genotypes in ESBL-producing E. coli isolated from children with community-acquired UTI.METHODS: This was a prospective study conducted from November 2012 to March 2016 in a tertiary care center. E. coli isolated in urine cultures from children aged ≤18 years was identified and confirmed for ESBL production. ESBL-positive strains were screened for ESBL encoding genes. Chi-square test and Fisher’s exact test were used to compare the difference in antibiotic susceptibility with respect to ESBL positive and negative, and binary logistic regression was used to identify the risk factors associated with ESBL production.RESULTS: Among 523 E. coli isolates, 196 (37.5%) were ESBL positive, >90% were resistant to cephalosporins, and 56% were resistant to fluoroquinolones. Least resistance was observed for imipenem, netilmicin, and nitrofurantoin (2%, 8.6%, 15.3%). Association between ESBL production and drug resistance was significant for ceftazidime (P < 0.001), cefixime (P < 0.001), cefotaxime (P = 0.010), ceftazidime-clavulanic acid (P < 0.001), levofloxacin (P = 0.037), and gentamicin (P = 0.047) compared to non-ESBL E. coli. CTX-M gene was the most prevalent (87.5%), followed by TEM (68.4%) and SHV (3.1%). Previous history of UTI and intake of antibiotics were the common risk factors.CONCLUSION: ESBL-producing E. coli from community-acquired pediatric UTI carries more than one type of beta-lactamase coding genes correlating their increased antibiotic resistance. Aggressive infection control policy, routine screening for detecting ESBL isolates in clinical samples, and antimicrobial stewardship are the keys to prevent their dissemination in community settings.
Keywords: Cefotaximase; community-acquired pediatric urinary tract infection; extended-spectrum beta-lactamase; sulfhydryl variable, temoneira